2006
DOI: 10.1080/17402520600645712
|View full text |Cite
|
Sign up to set email alerts
|

HIV‐1 Tat Triggers TGF‐β Production and NK Cell Apoptosis that is Prevented by Pertussis Toxin B

Abstract: Herein, we show that PTX-B and its non-toxic mutant PT9K/129G inhibit transcription and secretion of TGF-b elicited by HIV-1 Tat in NK cells. Moreover, Tat strongly activates the cJun component of the multimolecular complex AP-1, while TGF-b triggers cFos and cJun. Treatment of NK cells In turn,with PTX-B or PT9K/129G inhibits Tat and TGF-b-induced activation of AP-1. TGF-b enhances starvation-induced NK cell apoptosis, reduces the transcription of the antiapoptotic protein Bcl-2 and inhibits Akt phosphorylati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 13 publications
1
31
0
Order By: Relevance
“…Interestingly, this NK cell expansion is not observed in chronic untreated patients, despite the fact that they exhibit reduced CD4+ T cell numbers as well, however, these individuals also exhibit high levels of viral replication and persistent immune activation, due to microbial translocation 8 , through accessory cells 40 . This hyper-activation, however, may drive direct NK cell apoptosis 47 , thereby preventing the observed increase of these cytolytic effector cells within tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this NK cell expansion is not observed in chronic untreated patients, despite the fact that they exhibit reduced CD4+ T cell numbers as well, however, these individuals also exhibit high levels of viral replication and persistent immune activation, due to microbial translocation 8 , through accessory cells 40 . This hyper-activation, however, may drive direct NK cell apoptosis 47 , thereby preventing the observed increase of these cytolytic effector cells within tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The transactivating effects of Tat are not limited to HIV-1-infected cells because the extracellular Tat protein, released from virus-infected cells, is able to enter uninfected cells and exert its activity directly on responsive genes (Ju et al, 2009). The upregulation of cellular genes by Tat consequently induces additional effects, such as apoptosis induction and immunosuppression (Gupta et al, 2008;Poggi & Zocchi, 2006;Bannasser & Bahraoui, 2002;Zheng et al, 2005), which will be discussed later.…”
Section: Tat-induced Modulation Of Cellular Gene Expressionmentioning
confidence: 99%
“…Gupta et al (2008) have shown that Tat suppresses gp120-specific T-cell response in an IL-10-dependent manner and the immunosuppressive effect of Tat is not observed in IL-10-deficient mice. Although they have suggested that the immunosuppressive effect of Tat is mediated through IL-10, it seems that Tat may adopt several strategies to suppress the immune system of HIVinfected individuals (Barton et al, 1996;Gallo, 1999;Miura et al, 2003;Poggi & Zocchi, 2006;Zheng et al, 2005).…”
Section: Immune Suppression By Tatmentioning
confidence: 99%
See 2 more Smart Citations